The Management Model of Religious Moderation at Istiqlal Mosque, Jakarta: An Analysis Based on Qur’anic Values - Bukhori Sail Attahiry (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine how the values of religious moderation sourced from the Qur'an are integrated in the management model of the Istiqlal Mosque, as well as analyze the effectiveness of its application in institutional governance, da'wah programs, and congregational services. This research uses a qualitative method with the type of case study research and phenomenological approach, through data collection techniques in the form of observation, in-depth interviews, and documentation studies. The results of the study show that the Istiqlal Mosque consistently applies the values of tawassuṭ, tasāmuḥ, and i'tidāl in its management through program innovations such as the Istiqlal Learning Center (ILC), civilization diplomacy, strengthening Qur'anic literacy, and inclusive and professional public services. This management model has proven to be able to strengthen Istiqlal's role as the center of moderate Islamic civilization that is adaptive, modern, and oriented towards the benefit of the ummah. This research is useful as a theoretical reference in the development of the management of religious institutions based on religious moderation and as a practical inspiration for other mosques in building governance that is inclusive, harmonious, and in harmony with the values of the Qur'an.